The Effect of Financial Stability, External Pressure, and Nature of Industry on Financial Statement Fraud: Evidence from FMCG Companies in the Consumer Non-Cyclicals Sector Listed on the Indonesia Stock Exchange (2019–2023) - 'Adawiyah, Siti Aulia; Rizky Shiyammurti, Nastiti (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Financial statement fraud is a deliberate act of manipulation that is carried out deliberately so as to reduce the reliability of financial information and has the potential to mislead stakeholders in economic decision-making. This study aims to analyze the influence of financial stability, external pressure, and nature of industry on financial statement fraud in Fast Moving Consumer Goods (FMCG) companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. A quantitative research design was employed using secondary data collected from companie’s annual financial statements. Sample selection was carried out using a purposive sampling method based on predetermined criteria that 150 research observations were obtained. Data analysis was carried out using logistic regression. The results of the study show that financial stability and external pressure have an effect on financial statement fraud, while the nature of industry has no effect on financial statement fraud. In addition, simultaneously financial stability, external pressure, and the nature of industry affect financial statement fraud. These findings show that the pressures faced by companies in maintaining financial stability and meeting external demands can increase the risk of financial statement fraud. These findings may serve as useful insights for companies, investors, and regulators in strengthening monitoring mechanisms and mitigating fraud risk in increasing supervision and supporting early detection efforts against potential financial statement fraud.